Integration and sustainability of cities - The case of Kuala Lumpur - Asma Abdul Rahman; N Yusoff; I Afida (UiTM Skudai, Johor, 2024)
Cities are nothing more than people, their activities, the spaces that people and their activities occupies, or better known as land uses, and the systems that allows them to interact, generically termed as transportation. Cities are deemed to be efficient when its components are in harmonious interaction with one another. More often than not, cities are plagued with numerous problems. Unemployment, crime, traffic congestion, squatters and overcrowding, pollution, etc are common in cities the world over. City components are not only internally disaggregated, but are often in conflict with one another. Indiscriminate utilization of land, the competition for survival and existence, results in neglect of the environment, affecting the sustainability of cities. Kuala Lumpur is no exception. In anticipation of the pressure for growth and development, the need to provide for human needs, the elimination of problems and the creation of a more livable city for its future generation, Kuala Lumpur embarked on its Kuala Lumpur Structure Plan Review 2020. The Kuala Lumpur Plan 2020 formulated 182 different policies to cover 13 different aspects of the plan, covering areas such as economic base and employment, income and quality of life, infrastructure and quality of life, commerce and industry, tourism, housing and squatters, urban design and landscapes, environment, etc. Playing the role of a premier city of the nation, Kuala Lumpur believes that it must contribute strongly to the attainment of the ideal embodied within the countrys Vision 2020. Kuala Lumpur set to become a world class city by 2020 in the areas of Living Environment, Working Environment, Business Environment and City Governance. This paper presents the findings and recommendations of the Kuala Lumpur Plan to secure the short term and the long term growth and sustainable development of Kuala Lumpur. It will summarize the issues and policies of different sectors. Particular attention will be given to the issue of integration of the key components of the plan, particularly, housing, commerce and industry and, traffic and transportation, in a bit to secure sustainability.